Rare book librarianship an introduction and guide - Galbraith, Steven Kenneth; Smith, Geoffrey D. (Geoffrey Dayton) 1948-. (Santa Barbara, Calif. Libraries Unlimited, 2012)
"Successfully managing rare book collections requires very specific knowledge and skills. This handbook provides that essential information in a single volume"--Provided by publisher.
Keywords: Rare book librarianship; Libraries -- Special collections -- Rare books; Rare books -- Bibliography -- Methodology; Rare book libraries -- Administration